2009
DOI: 10.1097/ccm.0b013e3181962316
|View full text |Cite
|
Sign up to set email alerts
|

Impact of continuous venovenous hemofiltration on organ failure during the early phase of severe sepsis: A randomized controlled trial*

Abstract: These data suggest that early application of standard continuous venovenous hemofiltration is deleterious in severe sepsis and septic shock. This study does not rule out an effect of high-volume hemofiltration (>35 mL/kg/hr) on the course of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
191
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(207 citation statements)
references
References 34 publications
5
191
1
10
Order By: Relevance
“…Unlike HVHF, standard 'renal dose' continuous renal replacement therapy (CRRT) appears to be in effective as an immune modulating therapy. Like Cole and colleagues [36] in 2002, Payen and colleagues [37] found no difference (and even a trend toward worse outcomes) between septic shock patients who did not have acute kidney injury and who underwent CVVH (25 mL/kg per hour for a 96-hour period) at the early phase of sepsis and those who were managed conventionally.…”
Section: High-volume Hemofiltrationmentioning
confidence: 99%
“…Unlike HVHF, standard 'renal dose' continuous renal replacement therapy (CRRT) appears to be in effective as an immune modulating therapy. Like Cole and colleagues [36] in 2002, Payen and colleagues [37] found no difference (and even a trend toward worse outcomes) between septic shock patients who did not have acute kidney injury and who underwent CVVH (25 mL/kg per hour for a 96-hour period) at the early phase of sepsis and those who were managed conventionally.…”
Section: High-volume Hemofiltrationmentioning
confidence: 99%
“…Furthermore, the early initiation of this intervention (isovolemic hemofiltration) may be very important. However, a randomized prospective study found that early intervention with low volume hemofiltration (25 mL/kg per hour) was deleterious in those with severe sepsis (37).…”
Section: Removal Of Immunomodulatory Substances In Sepsismentioning
confidence: 99%
“…A specific consideration should be done with respect to three studies comparing conservative treatment versus CVVH or high volume haemo-filtration (37,73), or in patients without ARF (8) respectively. Although it is doubtful whether these studies should be analysed together due to differences in design, a subgroup analysis did not reveal any subgroup effect.…”
Section: Efficacy Of Crrt In Patients With Severe Sepsis or Septic Shockmentioning
confidence: 99%
“…Furthermore, subsequent improvements with the use of hemofiltration, for example, were reported in both animal and human studies showing that inflammatory cytokines could be removed from the circulation in septic shock [6,7]. However, despite early promise, randomised controlled studies have failed to demonstrate any survival benefit from conventional or high volume hemofiltration [8,9]. Therapeutic plasma exchange (TPE) has also been used to modulate circulating levels of inflammatory cytokines, coagulation factors and endotoxin; however, despite positive preliminary data, less than 200 patients have been included in trials to date and additional studies are needed before this therapy can be routinely recommended [10].…”
mentioning
confidence: 99%
“…These therapies are not banal and without potential for adverse effects. For example, standard hemofiltration has been associated with worsening clinical status when applied as adjuncts to the treatment of sepsis [8]. Thus, the risk-benefit ratio of these techniques for many patients remains uncertain.…”
mentioning
confidence: 99%